Identification and genomic characterization of Pseudomonas spp. displaying biocontrol activity against Sclerotinia sclerotiorum in lettuce - Albert, Daphné; Zboralski, Antoine; Ciotola, Marie; Cadieux, Mélanie; Biessy, Adrien; Blom, Jochen; Beaulieu, Carole; Filion, Martin (Frontiers in Microbiology, 2024)
Lettuce is an economically major leafy vegetable that is affected by numerous diseases. One of the most devastating diseases of lettuce is white mold caused by Sclerotinia sclerotiorum. Control methods for this fungus are limited due to the development of genetic resistance to commonly used fungicides, the large number of hosts and the long-term survival of sclerotia in soil. To elaborate a new and more sustainable approach to contain this pathogen, 1,210 Pseudomonas strains previously isolated from agricultural soils in Canada were screened for their antagonistic activity against S. sclerotiorum. Nine Pseudomonas strains showed strong in vitro inhibition in dual-culture confrontational assays. Whole genome sequencing of these strains revealed their affiliation with four phylogenomic subgroups within the P. fluorescens group, namely P. corrugata, P. asplenii, P. mandelii and P. protegens. The antagonistic strains harbor several genes and gene clusters involved in the production of secondary metabolites, including mycin-type and peptin-type lipopeptides, and antibiotics such as brabantamide, which may be involved in the inhibitory activity observed against S. sclerotiorum. Three strains also demonstrated significant in planta biocontrol abilities against the pathogen when either inoculated on lettuce leaves or in the growing substrate of lettuce plants grown in pots. They however did not impact S. sclerotiorum populations in the rhizosphere, suggesting that they protect lettuce plants by altering the fitness and the virulence of the pathogen rather than by directly impeding its growth. These results mark a step forward in the development of biocontrol products against S. sclerotiorum.